Facile Preparation of Phosphotungstic Acid-Impregnated Yeast Hybrid Microspheres and Their Photocatalytic Performance for Decolorization of Azo Dye - Lan Chen; Bo Bai (International Journal of Photoenergy)
Phosphotungstic acid (HPW)-impregnated yeast hybrid microspheres were prepared by impregnation-adsorption technique through tuning pH of the aqueous yeast suspensions. The obtained products were characterized by field emission scanning electron microscopy (FE-SEM), energy dispersive spectrometry (EDS), X-ray diffraction (XRD), thermogravimetry-differential scanning calorimetry (TG-DSC), and ultraviolet-visible spectrophotometry (UV-Vis), respectively. FE-SEM and EDS ascertain that the HPW has been effectively introduced onto the surface of yeast, and the resulting samples retain ellipsoid shape, with the uniform size (length 4.5 ± 0.2 μm, width 3.0 ± 0.3 μm) and good monodispersion. XRD pattern indicates that the main crystal structure of as-synthesized HPW@yeast microsphere is Keggin structure. TG-DTA states that the HPW in composites has better thermal stability than pure HPW. Fourier transform infrared spectroscopy (FT-IR) elucidates that the functional groups or chemical bonds inherited from the pristine yeast cell were critical to the assembling of the composites. UV-Vis shows that the obtained samples have a good responding to UV light. The settling ability indicates that the hybrid microspheres possess an excellent suspension performance. In the test of catalytic activity, the HPW@yeast microsphere exhibits a high photocatalytic activity for the decoloration of Methylene blue and Congo red dye aqueous solutions, and there are a few activity losses after four cycles of uses.